Challenges of friction reduction of engine plain bearings – Tackling the problem with novel bearing materials. (March 2019) - Summer, Florian; Grün, Florian; Offenbecher, Martin; Taylor, Stuart
Abstract: This study specifically focuses on the friction properties of bearing materials. By means of laboratory test rigs using ring on disc and bearing segment systems extensive investigations under mixed friction conditions and start stop operation were carried out in this area. One the one hand, commonly used bearing products including bimetal and trimetal bearings with various coatings are studied resulting in elucidation of the underlying mechanisms of the friction performance. On the other hand, based on the conclusions thereof, novel bearing coatings are introduced and are verified regarding friction performance. The results emphasize the changing behaviour of the friction characteristics of bearing materials. Furthermore, the outstanding mixed friction capabilities of the herein proposed novel bearing coatings are documented. Highlights: A holistic characterization of bearing material friction is presented. Novel bearing materials are investigated regarding friction behaviour. Protective tribofilms (rich in P, O, Zn, S) form on novel SnCu bearing overlay. Optimized MoS2 and C distribution results in low friction for a polymer overlay.